2011
DOI: 10.1590/s0074-02762011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the synergistic potential of vancomycin combined with other antimicrobial agents against methicillin-resistant Staphylococcus aureus and coagulase-negative Staphylococcus spp strains

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) and coagulase-negative Staphylococcus spp (CNS) are the most common pathogens that cause serious long term infections in patients. Despite the existence of new antimicrobial agents, such as linezolid, vancomycin (VAN) remains the standard therapy for the treatment of infections caused by these multidrug-resistant strains. However, the use of VAN has been associated with a high frequency of therapeutic failures in some clinical scenarios, mainly with decreasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 17 publications
(21 reference statements)
0
31
0
2
Order By: Relevance
“…In two patients, no pathogen was identified during the first infection episode but during the second episode, (7) vanco (10) ceftazidime + vanco (15) vanco (46) vanco (38) vanco (24) teico (20) vanco (16) vanco (30) meropenem + vanco (30) ceftizoxime + tobramycin (12) vanco (48) bactrim (22) rifampin (14) vanco (58) The number of days after surgery that the symptoms began occurring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two patients, no pathogen was identified during the first infection episode but during the second episode, (7) vanco (10) ceftazidime + vanco (15) vanco (46) vanco (38) vanco (24) teico (20) vanco (16) vanco (30) meropenem + vanco (30) ceftizoxime + tobramycin (12) vanco (48) bactrim (22) rifampin (14) vanco (58) The number of days after surgery that the symptoms began occurring.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the drug might have not reached adequate concentrations at the appropriate sites 28) . It has been reported that increased bactericidal effects are observed when rifampin or trimethoprim/sulfamethoxazole are co-administered with vancomycin for a biomaterial infection caused by CoNS or S. aureus 29,30) . Since our patients had appropriate serum levels of vancomycin and the in- .…”
Section: Diagnosis Of Vp Shunt Infections In Children Ismentioning
confidence: 99%
“…The severe impact of antibiotic-resistant infections has led to the search for new and more efficient therapeutic applications [19,34,36,38]. Some of these methods include using pharmacodynamic synergism between two drugs against bacterial species.…”
Section: Discussionmentioning
confidence: 99%
“…VAN has a low degree of synergism with the antibacterial nisin against some S aureus strains [13]. Also, VAN has synergism with sulfamethoxazole/trimethoprim and rifampin against some Staphylococcus strains; however, when combined with imipenem and other drugs, VAN has synergistic effects against a broader range of methicillinresistant, coagulase-negative, and biofilm forms of Staphylococcus [30,34]. The synergism between CHX and VAN, like with the other examples mentioned, may ultimately allow for the reduced amount of total drug dosage clinically as well as greater antibiotic efficacy, coverage of multiple strains, and decreased incidence of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These coagulase negative strains (MRSA) have got approximately 90% of methicillin resistance due to β-lactam resistance (Silva et al, 2011). Story just not stopped here, but still it continues, some of the staphylococcal strains got resistance to the other drugs such as Vancomycin, which was previously widely used against the MRSA infections, and to treat infections of central nervous system, bone infections and sometimes for the pulmonary infections which require a more concentrations to get treated (Dehority, 2010).…”
Section: For Staphylococcus Aureus Mrsamentioning
confidence: 99%